2013
DOI: 10.1179/1743281212y.0000000044
|View full text |Cite
|
Sign up to set email alerts
|

Failure mode of HSLA/DQSK dissimilar steel resistance spot welds

Abstract: The failure mode of resistance spot welds (RSWs) (interfacial versus pullout) is a qualitative measure of RSW performance. Considering the adverse effect of interfacial failure mode on the vehicle crashworthiness, process parameters should be adjusted so that the pullout failure mode is guaranteed, ensuring reliability of spot welds during vehicle lifetime. In this paper, the microstructure and mechanical properties of dissimilar RSWs between HSLA420 and drawing quality specially killed low carbon steels are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…Increments in current resulted in increment in tensile shear strength (peak load).This is in line with the findings of many studies reported earlier, by various researchers [9,14]. It was noticed that, above a current value of 13 KA, increase in current resulted in decrease in peak load value, due to expulsion.…”
Section: Current and Tensile Shear Strengthsupporting
confidence: 92%
See 1 more Smart Citation
“…Increments in current resulted in increment in tensile shear strength (peak load).This is in line with the findings of many studies reported earlier, by various researchers [9,14]. It was noticed that, above a current value of 13 KA, increase in current resulted in decrease in peak load value, due to expulsion.…”
Section: Current and Tensile Shear Strengthsupporting
confidence: 92%
“…It is made up of copper-chromium alloy, and is water cooled type. A total of eight sets of trials were conducted, with current values ranging between 7 KA (Kilo Ampere) and 14 …”
Section: Welding Processmentioning
confidence: 99%
“…The lack interfacial failure of the tensile-shear results can be indicate that the optimum welding parameters were selected in this study. The failure mode of welded joints preferred as pull-out failure mode after the tensile-shear test [20,21].…”
Section: Tensile and Tensile-shear Testmentioning
confidence: 99%
“…It is well documented that the size of the fusion zone is the key physical weld attribute controlling the failuremode transition of spot welds. 5,[12][13][14][15][16][17][18][19] The effect of the welding current on the FZ size is shown in Figure 4 indicating an enlargement of the weld nugget by increasing the welding current and generating a higher heat at the sheet/sheet interface. According to Figure 4, the failure mode during the CT loading was changed from the IF to the PF by increasing the welding current and the FZ size.…”
Section: Failure Modementioning
confidence: 99%
“…The transition from the IF mode to the PF mode is generally related to the increase in the size of the fusion zone above the minimum value. 5,[14][15][16][17][18][19] There are several sizing criteria for resistance spot welds including industrial standards. The effectiveness of these criteria for evaluating an AHSS spot weld, however, was not adequately addressed in the automotive welding community; it was simply adopted from the mild-steel practice and applied to AHSS spot welds.…”
Section: Introductionmentioning
confidence: 99%